EVALUATION OF ISLAMIC EDUCATION LEARNING IN STRENGTHENING STUDENTS’ RELIGIOUS MODERATION AT SMP ISLAM TERPADU BANGKINANG - Diky Ardha Sundawa; Tumiran; Nurul Husna (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to evaluate the implementation of Islamic Religious Education (Pendidikan Agama Islam/PAI) learning in strengthening students’ religious moderation at SMP Islam Terpadu Bangkinang. Religious moderation is conceptualized as a religious attitude that emphasizes balance, tolerance, justice, and respect for diversity, which are essential values in maintaining social harmony within pluralistic societies. In the Indonesian educational context, Islamic Religious Education plays a strategic role not only in developing students’ religious knowledge but also in shaping moderate religious attitudes that prevent intolerance and extremism. Therefore, systematic evaluation of PAI learning is crucial to ensure that religious moderation values are effectively internalized by students. This study employs a qualitative approach with an evaluative research design to comprehensively examine how religious moderation values are integrated into PAI learning. The evaluation focuses on three main aspects: learning planning, learning implementation, and learning evaluation. Data were collected through classroom observations, in-depth interviews with Islamic Religious Education teachers and students, and documentation analysis of learning instruments such as lesson plans, syllabi, and assessment tools. These data collection techniques were employed to obtain an in-depth understanding of instructional practices, teacher–student interactions, and assessment strategies related to the cultivation of religious moderation values. Data analysis was conducted using an interactive model involving data reduction, data display, and conclusion drawing to ensure systematic and credible findings. The findings reveal that PAI learning at SMP Islam Terpadu Bangkinang has integrated religious moderation values into learning objectives and instructional planning. Teachers explicitly formulate learning goals that emphasize tolerance, balance, and mutual respect, while learning materials are contextualized to students’ social realities. During the learning implementation stage, teachers apply dialogical and participatory teaching methods, such as discussions and case-based learning, to encourage students to critically reflect on religious issues and social diversity. These approaches provide students with opportunities to understand differing perspectives and develop moderate religious attitudes in a reflective and respectful manner. However, the study also identifies several challenges in the implementation of religious moderation-based learning. The use of contextual and innovative instructional methods remains limited, and learning activities tend to rely on conventional approaches. Moreover, the evaluation of religious moderation attitudes has not yet been conducted systematically. Assessment instruments primarily focus on cognitive achievement, while affective and attitudinal dimensions—such as tolerance, openness, and balanced religious behavior—are not comprehensively measured using structured indicators or rubrics. This limitation affects the accuracy of evaluating students’ overall development of religious moderation. This study concludes that continuous and systematic evaluation of Islamic Religious Education learning is essential to enhance the effectiveness of strengthening religious moderation among students. The development of more comprehensive, contextual, and sustainable assessment instruments is necessary to holistically measure students’ cognitive, affective, and behavioral dimensions. In addition, the adoption of more dynamic and participatory instructional strategies is recommended to support deeper internalization of religious moderation values. The findings of this study contribute to the discourse on Islamic education and religious moderation by providing empirical insights into evaluative practices at the secondary school level and offering practical implications for improving PAI learning in pluralistic educational settings.